(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Congenital absence of patella(aplasia) or small size patella(hypoplasia) is very rare and usually associated with other anomalies like Nail Patella Syndrome, Ischiopatellar dysplasia and Turner-Kiesser syndrome. This condition can have diverse clinical manifestations. Congenitally absent patella is usually bilateral. The diagnosis of patellar aplasia and hypoplasia is often delayed because the patella is cartilaginous from birth till third and sixth years of age when it starts ossifying. We present a very unique and extremely rare case report of an isolated congenital absent patella on the right side and small sized patella on the left side in an adolescent and which was not associated with any syndrome.